Strategi manajemen reproduksi sapi di lahan kering Nusa Tenggara Timur - Ronny Markus Jami Riwu (Fakultas Pertanian Universitas Majalengka, 2025)
Beef availability is a key component of national food security, and East Nusa Tenggara (NTT) is one of Indonesia’s main cattle-producing regions with a challenging dryland ecosystem. However, prolonged drought, heat stress, and limited feed supply reduce reproductive efficiency, as reflected in high service per conception (S/C), long calving intervals (CI), variable conception rates (CR), and extended days open (DO). This review aims to analyze the reproductive constraints of cattle in NTT and identify adaptive management strategies to improve reproductive performance. A systematic literature review was conducted using full-text national scientific publications published within the last ten years that discuss reproductive indicators in NTT’s dryland systems. The findings show wide variation in reproductive performance across districts, with S/C ranging from 1.16–3.9, CR from 43.55–87.85%, and CI from 380–1003 days, influenced by nutritional deficits, heat stress, and traditional management practices. The adoption of reproductive technologies such as artificial insemination, estrus synchronization, sexed semen, and embryo transfer has been shown to increase conception rates up to 70% and shorten CI to 12–15 months. In conclusion, improving reproductive efficiency in NTT requires integrated reproductive biotechnology, strengthened estrus detection, improved nutritional management, and collaborative support from farmers, inseminators, extension agents, and local government to enhance productivity in dryland cattle systems.